2015
DOI: 10.1111/cei.12682
|View full text |Cite
|
Sign up to set email alerts
|

Epstein–Barr virus-specific CD8+ T lymphocytes from diffuse large B cell lymphoma patients are functionally impaired

Abstract: SummaryEpstein-Barr virus (EBV) is a persistent virus with oncogenic capacity that has been implicated in the development of aggressive B cell lymphomas, primarily in immunosuppressed individuals, although it can be present in immunocompetent individuals. Changes in the function and clonal diversity of T lymphocytes might be implied by viral persistence and lymphoma development. The aim of the present study was to evaluate the frequency, phenotype, function and clonotypical distribution of EBV-specific T cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
12

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 61 publications
0
18
1
12
Order By: Relevance
“…Notably, CTLA4 mutation carrier NK cells show defective effector functions, but normal peripheral maturation ( 28 ). Furthermore, EBV-specific CD8+ T cells in EBV-associated DLBCL ( CTLA4 wildtype) are functionally impaired, hence, CTLA-4 insufficiency might push the oncogenic capacity of EBV ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…Notably, CTLA4 mutation carrier NK cells show defective effector functions, but normal peripheral maturation ( 28 ). Furthermore, EBV-specific CD8+ T cells in EBV-associated DLBCL ( CTLA4 wildtype) are functionally impaired, hence, CTLA-4 insufficiency might push the oncogenic capacity of EBV ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a regulatory profile characterized both EBV+ and EBV− HL microenvironment 43 , which coexists with the immune effector cells. Previous reports have suggested that, in patients who develop lymphomas, EBV-specific subsets of circulating T cells are dysfunctional for IFN-γ secretion 44 , showing signs of immune exhaustion in association with increased soluble IL-10 levels 35 . Therefore, in our DLBCL series, cytotoxicity assessed by CD8+ cells and GrB+ expression could not be effective due to immune exhaustion, contributing to the pathogenesis of DLBCL.…”
Section: Discussionmentioning
confidence: 99%
“…The classical EBV+ DLBCL observed in the elderly is thought to arise as a consequence of an age-related senescence of EBV-specific T cell surveillance. The precise nature of the senescence-associated defects in T cell immunity have not yet been well defined, although a narrowing of the EBV-specific TCR-Vβ repertoire with reduced EBV-specific effector memory CD4 + and CD8 + T cell numbers has been described [ 86 ]. Consistent with reduced T cell immunity, these tumours usually display a Latency III viral gene expression profile [ 87 ], similar to that seen in the B-LPD lesions arising in immunosuppressed transplant recipients or in late-stage AIDS.…”
Section: Diffuse Large B Cell Lymphomamentioning
confidence: 99%